A [beta]-Amylase in Potato Tubers Is Induced by Storage at Low Temperature. - Nielsen, T. H. (1997)
A new starch-degrading enzyme activity is induced by storage of potato (Solanum tuberosum L.) tubers at low temperatures (L. Hill, R. Reimholz, R. Schroder, T.H. Nielsen, M. Stitt [1996] Plant Cell Environ 14: 1223-1237). The cold-induced activity was separated from other amylolytic activities in zymograms based on iodine staining of polyacrylamide gels containing amylopectin. A similar band of activity was detected at normal growth temperatures in leaves, stems, and growing tubers but was present only at low activity in warm-stored tubers. The cold-induced enzyme was separated by ion-exchange chromatography from other amylolytic activities. It has a broad neutral pH optimum. Characterization of its hydrolytic activity with different substrates showed that the cold-induced activity is a [beta]-amylase present at low activity in tubers stored at 20[deg]C and induced progressively when temperatures are decreased to 5 and 3[deg]C. The first clear induction of [beta]-amylase activity was observed within 3 d of storage at 3[deg]C, and the activity increased 4- to 5-fold within 10 d. The possible involvement of the cold-induced [beta]-amylase in sugar accumulation during cold storage is discussed.